Management of Post-parturient Haemoglobinuria in a Primiparous HF Cow using Whole Blood Transfusion as an Alternative Approach - Ajith , Lal P; Daund, Sushant S; Singh, Nikita; Kumar, Rajesh; Alam, Kabir (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Post-parturient haemoglobinuria is a sporadic condition seen world-wide, most commonly affects high-yielding dairy cows at the onset of lactation. It is characterized by development of acute intravascular haemolysis often associated with haemoglobinuria leading to potentially life-threatening anaemia. Beef and non-lactating cattle are rarely affected. The exact cause is unknown, but phosphorus depletion or hypophosphatemia, as well as copper deficiency and possibly haemolysing substances contained in certain feeds have been incriminated as potential causative or risk factors. Severe intracellular phosphorus depletion of RBCs is known to increase their osmotic fragility possibly predisposing to intravascular haemolysis. Blood transfusion is the first line of therapy in the treatment of animal which is suffering from various types of haemorrhage or blood loss. Blood transfusion is the transfusion of the whole blood or its components (blood cells or plasma) obtained from a healthy animal (donor) to another animal (recipient) whose blood is deficient in quantity and quality. This report documents such a clinical case in HC crossbred cow that was managed successfully with blood transfusion.
Keywords: Post-parturient; Haemoglobinuria; Transfusion